Age-Related Yield of Adipose-Derived Stem Cells Bearing the Low-Affinity Nerve Growth Factor Receptor - Raquel Cuevas-Diaz Duran; Maria Teresa González-Garza; Alejandro Cardenas-Lopez; Luis Chavez-Castilla; Delia Elva Cruz-Vega; Jorge E. Moreno-Cuevas (Stem Cells International)
Adipose-derived stem cells (ADSCs) are a heterogeneous cell population that may be enriched by positive selection with antibodies against the low-affinity nerve growth factor receptor (LNGFR or CD271), yielding a selective cell universe with higher proliferation and differentiation potential. This paper addresses the need for determining the quantity of ADSCs positive for the CD271 receptor and its correlation with donor's age. Mononuclear cells were harvested from the lower backs of 35 female donors and purified using magnetic beads. Multipotency capacity was tested by the expression of stemness genes and through differentiation into preosteoblasts and adipocytes. A significant statistical difference was found in CD271+ concentrations between defined age intervals. The highest yield was found within women on the 30–40-year-old age range. CD271+ ADSCs from all age groups showed differentiation capabilities as well as expression of typical multipotent stem cell genes. Our data suggest that the amount of CD271+ cells correlates inversely with age. However, the ability to obtain these cells was maintained through all age ranges with a yield higher than what has been reported from bone marrow. Our findings propose CD271+ ADSCs as the primary choice for tissue regeneration and autologous stem cell therapies in older subjects.